Comparative diagnostic accuracy of clinical screening instruments for diabetic peripheral neuropathy against vibration perception threshold: A study in Indonesia - Nunung Khairun Nissa Oper; Heri Kristianto; Laily Yuliatun; Rulli Rosandi (Nursing and Health Sciences Journal (NHSJ), 2026)
Diabetic peripheral neuropathy (DPN) is a major precursor of foot ulceration and amputation; however, validated low-cost screening tools remain limited in Southeast Asian populations. This study evaluated and compared the diagnostic accuracy of the MNSI-A, MNSI-B, DNS, and DNE against biothesiometer-defined DPN in Indonesian adults with type 2 diabetes. A cross-sectional diagnostic accuracy study recruited 140 consecutive patients with type 2 diabetes at Lavalette Hospital in Malang between August and September 2023. Two trained assessors administered the MNSI-A, MNSI-B, DNS, and DNE under double-anonymized conditions. A biothesiometer vibration perception threshold >15 V at the great toe served as the reference standard. Sensitivity, specificity, predictive values, and overall accuracy were calculated with 95% confidence intervals (CIs). DPN was detected in 55 (39.3 %) patients. MNSI-B showed the highest performance, with a sensitivity of 85.4% (95% CI 73.4–92.9), specificity of 97.6% (95% CI 91.4–99.7), positive predictive value of 95.9%, negative predictive value of 91.2%, and overall accuracy of 92.8%. The MNSI-A had a sensitivity of 76.3% (63.3–85.9) and specificity of 90.5% (82.1–95.3). The DNS yielded a sensitivity of 74.5% (61.3–84.5) and specificity of 72.9% (62.4–81.5). DNE showed a sensitivity of 83.6% (71.6–91.4) and specificity of 78.8% (68.6–86.6). The MNSI-B demonstrated excellent accuracy and may serve as a practical, low-cost first-line DPN screening instrument in Indonesian clinical settings. Symptom-based tools should not be used alone and should be integrated with objective physical examinations. These findings support the implementation of structured physical examinations in diabetes foot care programs.